Structural, thermal and dissolution properties of MgO- and CaO-containing borophosphate glasses: effect of Fe2O3 addition - Tan, Chao; Ahmed, Ifty; Parsons, Andrew J.; Sharmin, Nusrat; Zhu, Chenkai; Liu, Jinsong; Rudd, Chris D.; Liu, Xiaoling (Springer, 2017)
This paper investigated manufacture of high-durability phosphate glass fibres for biomedical applications. Five different borophosphate glass formulations in the systems of 45P2O5–5B2O3–5Na2O–(29 − x)CaO–16MgO–(x)Fe2O3 and 45P2O5–5B2O3–5Na2O–24CaO–(21 − x)MgO–(x)Fe2O3 where x = 5, 8 and 11 mol% were produced via melt quenching. The compositions and amorphous nature of the glasses were confirmed by ICP-MS and XRD, respectively. FTIR results indicated depolymerisation of the phosphate chains with a decrease in Q2 units with increasing Fe2O3 content. DSC analyses showed an increase in Tg by ~5 °C with an increment of 3 mol% in Fe2O3 content. The thermal properties were also used to calculate processing window (i.e. Tc,ons—Tg) and another parameter, Kgl, to determine the suitability for fibre drawing directly from melt, which equals (Tc,ons—Tg)/(Tl—Tc,ons). The degradation study conducted in PBS solution at 37 °C showed a decrease of 25–47% in degradation rate with increasing Fe2O3 content. This confirmed that the chemical durability of the glasses had increased, which was suggested to be due to Fe2O3 addition. Furthermore, the density measured via Archimedes method revealed a linear increase with increasing Fe2O3 content.